The Influence of Overconfidence, Emotional Biases, and Social Media on Stock Market Investment Decisions During Periods of Economic Uncertainty : Implications for Government Economic Policy - Singh, Shivalee; Kotrba, Vojtěch; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the influence of psychological biases, particularly overconfidence and emotional reactions, alongside sentiment shaped by social media, on investor choices during periods of heightened economic and geopolitical uncertainty. This research is grounded in theoretical frameworks of behavioural economics and investigates investor behaviour across three empirical dimensions: the relationship between the VIX index and global stock market returns, institutional trading patterns obtained from the Deutsche Börse A7 platform, and sentiment analysis extracted from Reddit, Twitter, and WallStreetBets (WSB) during the COVID-19 pandemic, the Russia–Ukraine War, and the stock market decline of 2022. The results demonstrate a notable inverse correlation between the VIX and stock index returns, especially in developed markets such as the S&P 500 and DAX. This finding substantiates the theory that heightened market anxiety is associated with reduced equity performance. The COVID-19 crisis saw a significant rise in institutional trading volume, particularly in large-cap indices, reflecting a behavioural inclination towards herding and an increased sense of risk aversion among market participants. The relationship between sentiment from Reddit and WallStreetBets (WSB) and the CNN Fear and Greed Index was significantly strong during the COVID-19 pandemic; however, this correlation weakened during the Ukraine conflict. This finding indicates that the impact of sentiment depends on the particular characteristics of the crisis and the emotional reactions it provokes. The findings detailed in this work contribute to the current literature by offering empirical support for behavioural economic concepts such as loss aversion, bounded rationality, and emotional contagion within real market settings.
The thesis asserts that behavioural indicators, particularly sentiment metrics and institutional volume patterns, can enhance market oversight and inform government policy during crises.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses